Fenomena Mandi Lumpur : Analisis Multidisiplin dan Relevansi Hadist Larangan Berbuat Zholim - Rizal; Risko Ari Saputra (Jurnal Riset Multidisiplin Edukasi, 2026)
This study examines the phenomenon of the exploitation of vulnerable communities on digital platforms, specifically the practice of "online begging" on TikTok, through the reactualization of the Hadith Qudsi on the prohibition of injustice (dhulm). In the midst of rapid digitalization, human suffering is frequently commodified into profane entertainment content, signaling a moral crisis in cyber-space. This research aims to dissect this phenomenon not merely as a common ethical violation, but as a form of systemic injustice that disrupts the social order. Utilizing a multidisciplinary approach, this study integrates three scholarly perspectives: Émile Durkheim’s sociology to observe the decay of social solidarity, John Rawls’s philosophy to criticize the disparity of justice (fairness), and Imam al-Shatibi’s Maqāṣid al-Syarī‘ah to evaluate the violation of the hierarchy of human welfare. The results indicate that digital exploitation is a form of injustice that prioritizes the acquisition of wealth over the protection of life and human dignity (Hifz al-Nafs). This research concludes that the Hadith on the prohibition of injustice must be transformed from a mere normative text into a practical guide to reconstruct the character of digital citizens to be more humane, just, and compliant with the priority scale of public interest over individual materialistic ambitions.